Nivel de conocimiento y actitud sobre normas de bioseguridad en enfermeras del servicio cirugía Hospital Regional Docente de Trujillo 2012 - Pérez Medina, Karina Yesabel (2012)
This research study, descriptive correlational, was conducted in the surgery department of the Regional Hospital of Trujillo, in order to determine the relationship between the level of knowledge and attitudes about biosecurity standards in nurses. The sample universe is consisted of 21 nurses, who are including in the inclusion criterion. For data collection we used two instruments: Test to determine the level of knowledge about biosecurity standards and the Test to determine the attitude of biosecurity standards. The results are presented in league tables of single and double frequency with numerical and percentage data, as well as statistical graphics. The results are that 57.1% had a regular level of knowledge on biosecurity standards, and 42.9% had a good level of knowledge. Also 61.9% of nurses presented a regular attitude on biosecurity standards, while 38.1% had a good attitude, and finally 100% of nurses who had a regular level of knowledge on biosecurity, have a regular attitude, while the 88.9% of nurses had a good level of knowledge, had a good attitude. The analysis of the relationship between variables was conducted by the test of Chi Square (X ²), its result was 17.23 with a probability of 0.000, and it was highly significant therefore there is a relationship between variables.